The genus Schiffnerula on Asteraceae in Kerala, India - and M.C. RIJU, V.B. HOSAGOUDAR*, A. SABEENA (Indian Phytopathology, 2010)
This paper gives an account of four new species, namely, Schiffnerula ecliptae on Eclipta alba, S. spilanthi onÂ Spilanthes radicans, S. vernoniae on Vernonia anthelmintica and S. wedeliae on Wedelia chinensis, collected respectively, fromÂ the Western Ghats region of Kerala state are described and illustrated in detail.